"WasserSportwissenschaft online" - theoretical considerations and practical experiences on the way to a virtual learning environment - Hebbel-Seeger, A.; Koch, B. (International Journal of Computer Science in Sport, 2003)
The project "Wassersportwissenschaft online" is a virtual learning environment that has been developed as a support of direct learning within the framework of the theory- practical classes in regard to the marine sports rowing, canoeing, sailing, and surfing in the sports science faculty at the University of Hamburg. In this article we want to reflect on our concrete experiences with the concept, realisation and also the use of the named learning environment leading from theoretical learning suppositions and general expectations to the use of virtual learning environments. Besides the depiction of didactic-methodical decisions that are mainly orientated on the theory of constructivism which gives the elements construction, collaboration and reflection a central status with regard to the design of a learning process (cf. Hron/Hesse/Reinhard/Picard, 1997; Fischer/Bruhn/Gräsel/Mandl, 1998; Reinmann-Rothmeier/Mandl, 1999), we are especially going to have a closer look at practical experiences within the framework of the realisation. This area consists of two parts on the one hand thoughts in allusion to the programme structure, content and elements of interaction and on the other hand the suitability of certain file formats for the integration of multimedia content.